Development of activated carbon for textile wastewater bioremediation system [electronic resource] - 445196 Muhammad Mat Junoh @ Yunus; Fakulti Kejuruteraan Mekanikal (2008)
Thesis (Sarjana Kejuruteraan (Mekanikal)) - Universiti Teknologi Malaysia, 2008